Binge eating and binge eating disorder in athletes: a review of theory and evidence - Williams, G. (The Sport Journal, 2016)
Prevalence rates binge eating disorder (BED) among athletes are thought to be considerably higher than that of the general population due to strict requirements for weight and performance gains related to body composition. Traditional models of BED are based on the general population and are therefore unlikely to fully account for the development of BED in athletes, who typically display significant cognitive and dietary restraint. This review explores the scientific literature relevant to the development of BED in athletes which indicates that 1) Extreme, rigid dieting practices and preoccupation with body weight and composition is a risk factor for BED; 2) Prolonged caloric restriction with or without stressors disrupts hunger and satiety cues, results in abnormalities in neurotransmitter systems and alters fronto-striatal circuitry, driving urges to binge eat; and 3) BED shares several mechanisms and behavioural traits with drug addiction. At this time, no guidelines for the management of BED in athletes exist, and current treatments do not address the individual requirements of athletes. Knowledge that BED in athletes is likely driven by caloric restriction and multiple stressors may assist coaches and athletes in preventing the onset of BED, reducing the risk of associated psychological comorbidities and alterations in metabolism.